Ultrasonographic predictors for clinical and radiological progression in knee osteoarthritis after 2 years of follow-up. (23rd June 2015) - Bevers, Karen; Vriezekolk, Johanna E.; Bijlsma, Johannes W. J.; van den Ende, Cornelia H. M.; den Broeder, Alfons A.
Abstract : Objective. The aim of this study was to investigate the association between a set of US features and radiographic and clinical progression of knee OA after 2 years of follow-up. Methods. A total of 125 patients fulfilling ACR clinical criteria for knee OA underwent US examination of the most symptomatic knee. The US protocol included assessment of synovial hypertrophy, joint effusion, infrapatellar bursitis, Baker's cyst, medial meniscus protrusion and cartilage thickness. Clinical progression was defined using the inverse Osteoarthritis Research Society International responder criteria or progression to total knee replacement. Radiological progression was defined as a ≥2 point increase in Altman score or progression to total knee replacement. Regression analyses were performed with baseline ultrasonographic features as independent variables and progression (two separate models for clinical progression and radiographic progression) as the dependent variable. Results. A total of 31 (25%) patients fulfilled the criteria of clinical progression and 60 (48%) patients fulfilled the criteria of radiological progression. The presence of Baker's cyst showed a statistically significant association with clinical [odds ratio (OR) 3.07 (95% CI 1.21, 7.78)] as well as radiological [OR 2.84 (95% CI 1.17, 6.90)] progression. Synovial hypertrophy showed a weaker but consistent association with clinical as well as radiological progression [OR 2.11 (95% CI 0.80, 5.57)]. Conclusion. We demonstrated a longitudinal association between Baker's cyst (and to a lesser extent synovial hypertrophy) at baseline and radiological and clinical progression after 2 years.